Design and parametric analysis of a planar array antenna for circular polarization. Issue 6 (18th March 2015) - Rahman, Muhammad Asad; Hossain, Quazi Delwar; Hossain, Md. Azad; Nishiyama, Eisuke; Toyoda, Ichihiko
Abstract : A new circularly polarized planar array antenna using linearly polarized microstrip patches is designed and optimized for X-band wireless communication applications. Four square patch elements with feed network are used to design the circularly polarized array antenna. The feed network consists of microstrip lines on the obverse side of the dielectric substrate and slot line on the reverse side of the substrate. Both-sided MIC technology is successfully employed to apply its inherent advantages in the design process of the array structure. The unequal feed line is used to create 90° phase difference between the linearly polarized patches. Therefore, the circular polarization is realized by the combination of linearly polarized patches and unequal feed line. Characteristics of the proposed array are investigated by using two electromagnetic (EM) simulators: advanced design system and EMPro. The −10 dB impedance bandwidth of the antenna is around 5%. The 3 dB axial ratio bandwidth of 1.48% is obtained. The design of the proposed antenna along with parametric study is presented and discussed.